2019
DOI: 10.1161/circulationaha.119.041627
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Cardiac Troponin I Increase and Incident Mortality and Cardiovascular Events

Abstract: Background: Blood concentrations of cardiac troponin above the 99 th percentile are a key criterion for the diagnosis of acute myocardial injury and infarction. Troponin concentrations, even below the 99 th percentile, predict adverse outcomes in patients and the general population. Elevated troponin concentrations are commonly observed after endurance exercise, but the clinical significance of this increase is unknown. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 36 publications
4
72
0
5
Order By: Relevance
“…A very recent study by Aengevaeren et al also assessed long-term outcomes of exercise-induced cTnI increase (83). In this study, a highly significant association was identified between all-cause mortality and major adverse cardiovascular events, and cTnI increase above the upper reference limit following a prolonged walking exercise in 725 participants (83).…”
Section: Cardiac Troponinsmentioning
confidence: 69%
See 2 more Smart Citations
“…A very recent study by Aengevaeren et al also assessed long-term outcomes of exercise-induced cTnI increase (83). In this study, a highly significant association was identified between all-cause mortality and major adverse cardiovascular events, and cTnI increase above the upper reference limit following a prolonged walking exercise in 725 participants (83).…”
Section: Cardiac Troponinsmentioning
confidence: 69%
“…Cardiac troponins are markers of myocardial injury, and increased levels have been associated with increased risk of cardiovascular mortality and morbidity, recently also following exercise (83). This biomarker is therefore of major interest in detecting potentially pathological responses to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this feature allows assessment of a homogeneous cohort, free of potential confounding issues associated with training status or health status. 25 In addition, a new stricter luteal phase verification limit of >16 nmol l −1 for progesterone has just been proposed. 23 It is, therefore, recommended that future research follow this criterion to reduce the risk of inclusion of anovulatory or luteal phase deficient cycles in a large and heterogeneous cohort.…”
Section: Mce Fpmentioning
confidence: 99%
“…Cardiac troponin I (cTnI) and T (cTnT) are regulatory proteins in cardiac tissue that regulate actin and myosin calcium-mediated interactions. 4 It is a protein that aids in the contraction of cardiomyocytes. Troponin is a heterotrimeric protein consisting of a tropomyosin-binding subunit troponin T (TnT), a Ca 2+ -binding subunit, troponin C (TnC), and a troponin I (TnI) inhibitory subunit.…”
Section: Introductionmentioning
confidence: 99%